1970
DOI: 10.1136/bmj.1.5698.713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thyopac-3 Test in the In-vitro Assessment of Thyroid Function

Abstract: DALOUNA 713either beyond the termination of a contraction or in susceptible subjects to the end of a contraction, will result in loss of consciousness at the amnesic level. With 70% nitrous oxide unconsciousness will occur sooner. Most mothers stated that the gas and oxygen machine helped them, and nearly three-quarters of them found that the help was complete or considerable; the replies of the midwives bear out these findings. Just over a quarter of the mothers, however, found the help inadequate, the figure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1970
1970
1978
1978

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…This is a distinct advantage in a busy laboratory, especially when the assay is being done by relatively inex-33 0 34 perienced personnel. Similar findings on the time dependence of the Thyopac test have been made by Clark and Brown (1970a). We have also found that the technique is less influenced by the temperature of incubation, and no correction is necessary for normal variations in laboratory temperature.…”
Section: Discussionsupporting
confidence: 87%
“…This is a distinct advantage in a busy laboratory, especially when the assay is being done by relatively inex-33 0 34 perienced personnel. Similar findings on the time dependence of the Thyopac test have been made by Clark and Brown (1970a). We have also found that the technique is less influenced by the temperature of incubation, and no correction is necessary for normal variations in laboratory temperature.…”
Section: Discussionsupporting
confidence: 87%
“…In the majority of pregnant women and in the TBG-deficient subject, the values for Thyopac-3 and -4 differed by more than 2 standard deviations from the mean normal value, corroborating previous observations (Clark and Brown, 1970a). …”
Section: Resultssupporting
confidence: 90%
“…The following thyroid function tests were carried out: thyroidal radioiodine uptake and scan, serum thyroxine (Murphy, 1965), T} resin uptake (Clark and Brown, 1970), serum triiodothyronine (Mitsuma et al. 1971) and thyroid-stimulating hormone (TSH) (Hall el at, 1971).…”
Section: Methodsmentioning
confidence: 99%